2020
DOI: 10.3390/ani10050794
|View full text |Cite
|
Sign up to set email alerts
|

Does the Degree of Fatness and Muscularity Determined by Ultrasound Method Affect Sows’ Reproductive Performance?

Abstract: The fatness and muscularity of Polish Landrace, Polish Large White gilts and sows and their hybrids were determined on the basis of ultrasound measurements in three consecutive parities, and then the relationship between these parameters and reproductive performance was established. Ultrasound measurements demonstrated the highest fat thickness in first parity and the highest fat area over LD muscle in hybrid gilts (PL × PLW). Pure-bred gilts were characterized by poorer muscularity. Fatness level affected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Furthermore, gilts mated at a high live weight will most likely experience compromised longevity due to locomotory problems. In contrast to growing/finishing pigs, increased body fatness is required for reproductive females, because sufficient body fatness may be favorable for the onset of puberty and future reproductive output (J. S. Kim et al, 2015; Knecht et al, 2020; Maes et al, 2004). With modern lean genotype gilts, the focus should, therefore, be to ensure sufficient backfat thickness at an optimal age and weight to maximize the sow's lifetime reproductive output.…”
Section: Prepubertal Giltsmentioning
confidence: 99%
“…Furthermore, gilts mated at a high live weight will most likely experience compromised longevity due to locomotory problems. In contrast to growing/finishing pigs, increased body fatness is required for reproductive females, because sufficient body fatness may be favorable for the onset of puberty and future reproductive output (J. S. Kim et al, 2015; Knecht et al, 2020; Maes et al, 2004). With modern lean genotype gilts, the focus should, therefore, be to ensure sufficient backfat thickness at an optimal age and weight to maximize the sow's lifetime reproductive output.…”
Section: Prepubertal Giltsmentioning
confidence: 99%
“…Another imaging approach that has been used to measure body and carcass composition is ultrasound [ 114 ]. This technique has been widely used to monitor body condition in small ruminants [ 115 , 116 ], in swine [ 117 ], and in cattle [ 118 ]. For dairy cows, recent studies [ 119 , 120 ] showed the relevance of using ultrasound to assess the body reserves of cows with ultrasonic measurement to scan the body regions that are connected to the BCS evaluation, such as the ribs, pin, tail-head, and lumbar spine.…”
Section: Welfare Of Dairy Cows and Precision Livestock Farmingmentioning
confidence: 99%
“…Thus, the variations of tWSI in primiparous sows might more closely be correlated with their body conditions at insemination, parturition and post-weaning and amount of BF loss during lactation. As the report of Knecht et al (2020) in Poland, the signi cant difference in weaning to service interval was observed between sows with different fatness degree at insemination. Under a well-feeding program, the sows would have an adequate fat store for fetal growth, milk production, rearing their young piglets and replenishing their fatty tissue loss during lactation that would be bene cial for recovering their body to rebreeding condition.…”
Section: Association Between Bf and Production Traitsmentioning
confidence: 62%